The quality of communication in teaching and students’ emotional reactions in the classroom - Stojanovic, Biljana; Cirkovic-Miladinovic, Ivana; Milovanovic, Radmila (Technium Social Sciences Journal, 2021)
One of the burning topics of theoretical considerations in pedagogy and education today is precisely the affective side of the educational process and related phenomena. Starting from the model of understanding learning and teaching, which includes considering the quality of communication and the role of emotions in educational practice, the main goal of the research was to examine the relationship between the quality of communication and emotional reactions of students in teaching and identify possible differences between students in Serbia, Hungary and Germany. The sample consisted of 303 students aged between 14 and 19 from Serbia, Germany and Hungary. The Shabot and Shabot (2009) Self-Assessment Questionnaire for Emotional Reactions in Teaching was used to collect data on students' emotional reactions. The results showed that students in the overall sample estimate that the quality of communication, emotional experience of teaching, the degree of involvement in work and the degree of connection with peers are at the middle level (M = 5.65 to 6.25). Statistically highly significant differences (p <0.001) were found in the type and intensity of the quality of communication in teaching, the degree of involvement in work and the degree of connection with peers between students from Serbia and Germany and Serbia and Hungary in almost all categories. No significant differences were found between the sexes and students of different ages. The results indicate the importance of the quality of communication and encouraging pleasant emotional reactions in teaching, as well as the need to create a positive emotional climate that would allow students greater engagement in the teaching process, which would be a topic for further research.